Site-specific incorporation of biophysical probes into proteins. - Cornish, V W (1994)
Biophysical probes which can detect structural changes in proteins and the interaction of proteins with other macromolecules are important tools in studying protein function. Many difficulties remain, however, in introducing probes into proteins site-specifically. Here we report the successful site-specific incorporation of a spin-labeled, a fluorescent, and a photoactivatible amino acid into a variety of surface and internal sites in bacteriophage T4 lysozyme by using unnatural amino acid mutagenesis. In addition, we report the purification and spectral characterization of T4 lysozyme mutants containing the spin-labeled amino acid and the fluorescent amino acid. The ability to incorporate these probes site-specifically allows for novel studies of protein structure and dynamics. Moreover, this work demonstrates that the Escherichia coli protein biosynthetic machinery can tolerate unnatural amino acids with little resemblance to the natural amino acids.